HUBUNGAN STRESS DENGAN PRE MENSTRUAL SYNDROME (PMS) DAN KUALITAS HIDUP NARAPIDANA PEREMPUAN DI LEMBAGA PEMASYARAKATAN KELAS IIB LUMAJANG - Fadilah, Nur; Sary, Yessy Nur Endah; Zakiyyah, Muthmainnah (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
When in correctional institutions, prisoners with many stressors who have a history of premenstrual syndrome certainly have various experiences in compensating for what they experienced, so it is important to dig deeper into the experiences experienced and felt by female prisoners in dealing with PMS. Stress that cannot be controlled and occurs prolonged and overwhelms and has a negative impact on individuals who are considered to affect the quality of life of female convicts while serving their sentence. The aim of this study was to determine the relationship between stress and premenstrual syndrome (PMS) and the quality of life of female convicts in prisons. Lumajang Class IIB Penitentiary. This research method used an analytic observational design with a cross-sectional approach. The sample is all 10 prisoners of Class IIB Lumajang Penitentiary. The sampling technique is total sampling. Data analysis used the Product Moment correlation calculation technique by Pearson. The results of this study indicate that there is a relationship between the stress variable and Premenstrual syndrome (PMS). The strength of the correlation is moderate (R = 0.599) and the correlation is not significant (Sig > 0.05). The results also showed no relationship between stress and quality of life. There is a relationship between stress and premenstrual syndrome (PMS) for female prisoners in the Class IIB Penitentiary in Lumajang, but there is no relationship between stress and the quality of life of female prisoners in the Class IIB Penitentiary in Lumajang. The results of this study should add insight, input and information to researchers about the problem of stress, premenstrual syndrome (PMS) and quality of life so that prisoners can minimize and prevent the occurrence of premenstrual syndrome (PMS).